Effect of the deviation of the current density profile center on the three-dimensional non-transferred arc plasma torch. (2nd July 2015) - Guo, Zhiwei; Yin, Shuo; Qian, Zhongdong; Liao, Hanlin; Gu, Sai
Highlights: The asymmetrical current density profile affects the plasma flow inside the torch. The temperature inside the plasma column reduce as the deviation distance increases. The velocity inside the plasma column reduce as the deviation distance increases. The arc length decreases as the deviation distance increases. Abstract: In this study, the three-dimensional steady-state non-transferred plasma arc was investigated using computational fluid dynamics (CFD) with user defined functions (UDFs). A two-equation current density profile was developed to simulate the complex plasma flow inside the torch. The effect of the deviation distance (distance between the cathode tip center and the current density profile center) on the plasma flow features was systematically investigated for the first time. It is found that the temperature and velocity inside the plasma column reduce as the deviation distance increases, but the temperature near the arc-root attachment shows an increasing trend. Besides, it is also found that the arc length decreases with increasing the deviation distance.